Touristech: desenvolvimento de um aplicativo turístico prático e inovador para o Centro Histórico de Olinda. - Souza, Tacila Estevam da Silva (2020)
This research project aimed to build a mobile tourist application for the historic site of Olinda (PE), in order to help tourists, both national and international, in getting around the beautiful streets of this city. This application was developed to work as much as possible offline and with possibilities of translation into other languages, eliminating the use of pamphlets and booklets that were not always able to guide travelers in a clear and objective way. For this objective to be achieved, it was necessary to carry out an extensive study on information and how it, through a combination of data, is transformed into knowledge (SHEDROFF, 1999; RIBEIRO, 2009; FERREIRA et. Al., 1999). It was necessary to understand the importance of information design, in view of technological advances, and its role in interpreting and organizing information to target it to its target audience (HORN, 1999; LIPTON, 2007). Understand about the design of interfaces and their role as mediator between the user and the artifact, checking the existing intersections between it and the information design (JOHNSON, 2001; LÉVY, 199; WINOGRAD, 1997; BAIRON, 1995; BONSIEPE, 1997). Based on authors such as ROTO (et. al., 2011), Russo and Hekkert (2008), Unger & Chandler (2009) and Nielsen (2012) it was possible to understand about the user experience (UX) and the importance of testing usability so that the product corresponds to the needs of its audience. And through authors (BARRETTO, 2003; DE LA TORRE, 1992; AMARAL JUNIOR, 2008; BADARÓ, 2005) a study was made about tourism, knowing its history and how it was transformed by information technology (BUHALIS, 2008; LEVITT, 1998). From these studies, Munari's methodology (2015) was used, identifying problems, collecting data and analyzing them, going through the product creation phase, testing it, making adjustments and reaching the solution: a tourist application location for the historic center of Olinda practical, precise, customizable and innovative.